Mortality and causes of death in people living with HIV in the era of combination antiretroviral therapy compared with the general population in Japan. (1st May 2020) - Nishijima, Takeshi; Inaba, Yosuke; Kawasaki, Yohei; Tsukada, Kunihisa; Teruya, Katsuji; Kikuchi, Yoshimi; Gatanaga, Hiroyuki; Oka, Shinichi
Abstract : Objectives: To determine the mortality and causes of death in people living with HIV (PLHIV) in Japan. Design: A prospective cohort study at AIDS Clinical Center, Tokyo, which treats approximately 10% of PLHIV in care in Japan. Methods: Either PLHIV who visited our center for the first time between January 2005 and December 2014 or PLHIV who started their regular visit before January 2005 and visited us between January and March 2005 were included and followed by the end of 2016. Causes of death were defined according to the CoDe protocol. Results: Two thousand, seven hundred and ninety-seven PLHIV were analysed with total of 18 858 person-years of follow-up, which constitutes 14% of the estimated number of PLHIV in care in Japan. One hundred and sixty-five (5.9%) PLHIV died with all-cause mortality rate of 8.75 per 1000 person-years. All-cause mortality rate for PLHIV in care in Japan was estimated to be 8.75 per 1000 person-years (95% CI 5.53–12.0). Among causes of death, AIDS-defining illnesses accounted for 39% and malignancy contributed to 47%. Standardized mortality ratio (SMR) for all-cause mortality, malignancy-related mortality, and suicide were 5.96 (95% CI 5.05–6.87), 7.76 (95% CI 6.02–9.51), and 3.24 (95% CI 1.54–4.94), respectively. Even among the patients who were diagnosed early or without history of AIDS, SMR was four times higher than the general population. Conclusion: Mortality of PLHIV, even among those with early diagnosis, is substantially higher than that of the general population in Japan, highlighting the importance of further efforts towards prevention, early diagnosis and prompt treatment initiation. Abstract : Supplemental Digital Content is available in the text